Cohesive element formulation for z-pin delamination bridging in fibre reinforced laminates - Mohamed, Galal; Allegri, Giuliano; Yasaee, Mehdi; Hallett, Stephen R. (Elsevier, 2017)
Z-pins are an effective method of reinforcing laminated composite materials for resisting the propagation of delamination. In this paper, a novel numerical method combines the classical cohesive finite element (FE) method with a semi-analytical z-pin crack bridging model. Special purpose cohesive elements, in which the generalized traction-displacement characteristics are provided by the semi-analytical model z-pin bridging map, are implemented in macro-scale FE models. This cohesive element offers the flexibility to employ two cohesive laws concurrently for prediction of delamination propagation, for both the pinned and unpinned behaviour. Its efficacy is evaluated by the simulation of double cantilever beam (DCB), mixed-mode bend (MMB), and pure mode II End-Loaded Split (ELS) fracture tests at 2% z-pin areal density. The numerical results in terms of load-deflection predictions agree well with experiments. The different simulations were all performed using a single set of input parameters derived from single z-pin tests with no fitting factors.
Keywords: Composite materials; Fibre reinforced; Delamination; Toughness